Structural Identification of Glycopeptides Derived from Chicken Egg White Proteins - CAI Zhihong, HE Hong, WANG Mei, WANG Yuting, LI Shugang, WANG Jinqiu, GENG Fang (Shipin Kexue)
The primary proteins in chicken egg white are glycoproteins, which generate substantial glycopeptides in the digestive tract following gastrointestinal digestion. The structures of the glycopeptides have yet to be identified and elucidated. In this study, chicken egg white was digested by trypsin, and N-glycopeptides were enriched from the hydrolysate by hydrophilic interaction chromatography and O-glycopeptides by retain AX chromatography combined with AminoLink resin adsorption. The structures of these glycopeptides were analyzed by liquid chromatography-mass spectrometry (LC-MS), and their potential intestinal effects were explored by bioinformatics analysis. Mass spectrometry analysis identified 1 720 N-glycopeptides from 49 N-glycoproteins and 565 O-glycopeptides from 29 O-glycoproteins. Glycopeptides derived from ovomucin were the most diverse, including 490 N-glycopeptides and 216 O-glycopeptides. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed that sialylated N-glycoproteins were mainly involved in interleukin-17 signaling pathway and ferroptosis, while sialylated O-glycoproteins were mainly involved in cholesterol metabolism, vitamin digestion and absorption, the hypoxia-inducible factor-1 signaling pathway and the renin-angiotensin system. This study provides crucial structural information for further research on the potential effects of egg white glycopeptides on the intestinal tract.